Ultimate showdown - Patterson, James, 1947-; Bergen, Julia (Patterson, James, 1947- Middle school novels., 2014)
Opinionated siblings Rafe and Georgia Khatchadorian debate a variety of topics relating to the ups and downs of middle school life and encourage readers to add their own contributions through write-in games and activities.